KEMAMPUAN PESERTA DIDIK KELAS VIII SMP NEGERI 1 TELAGA MENGIDENTIFIKASI UNSUR-UNSUR DRAMA DALAM PEMBELAJARAN BAHASA INDONESIA - Sri Gitawati Umar; Fatmah AR Umar; Herman Didipu (Jurusan Pendidikan Bahasa & Sastra Indonesia, Universitas Negeri Gorontalo, 2020)
This study aims to describe the ability of eighth-gradersin SMP 1 state junior high school of telaga in identifying the elements of drama in Indonesia Language Subject, the factors that inhibit the ability, and solutions to the inhibitors. This descriptive research collectsthe data using ability tests and questionnaires to measure the students' ability in identifying the elements of drama, obtaining an average of 67 categorized as